Interfacial reaction layer and tensile shear strength of AI 6063 alloy/stainless steel 316L spot welded joint - Mazlee, Mohd Noor; Shamsul Baharin, Jamaludin, Prof. Dr.; Ayusnida, S. (SIRIM, 2011)
4th Malaysian Powder Metallurgy Symposium (MPMS) and Malaysian Metallurgical Conference (MMC) 2010 organized by SIRIM Berhad on 22nd - 23rd November 2010 at Parkroyal Hotel, Penang, Malaysia.